Design of residential building is based on the accessibility of the elderly residents to the environment and building - Adriana Sugiharto (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2017)
The design of the elderly housing is increasingly needed, as a result life expectancy has improved which make the growth number of the elderly increases. Senior living for the elderly have had unfavorable image in the community because of a lack of attention to the design of the special needs of the elderly. Like providing the handrail around the wall to maintain the body balance when the elderly walking through the circulation way. The main issue is accessibility in elderly housing for the comfort mobility of the residents to do their daily activity. For that, this research has been done from the ergonomic and anthropometric theory base as a reference in the making of the accessibility comfort analysis. This research are aims to find out how to find senior living design consideration that prioritizes the accessibility comfort of elderly people in the fulfillment of convenience in specific design for everyday activities. Case studies are designed with a qualitative comparative method. Senior living research is taken in the form of photos documentation, notes, interviews and observation. Through the research results are expected to find senior living design guidelines for the elderly based on the building and the space arrangement for accessibility. These research efforts are to help for all those who want to enrich design learning about ideal accessibility in senior living design.